Structural Change and Bipolarization of Korean Agriculture - 김정호 (한국농촌경제연구원, 2006)
In the 1990s, the Korean agriculture has walked the path of bipolarization at a fast speed. While the majority farms are small-scale, a few large-scale farms account for most of the national agricultural production. The plain area agriculture, where the large-scale farming is very active, is growing, but the hilly & mountainous area agriculture, where the large-scale farming is inactive, is waning. The agricultural bipolarization is an inevitable phenomenon, which appears in the course of restructuring. It can improve agricultural structure, but at the same time, it can cause conflicts between classes or regions. Advanced countries have taken various policy measures to resolve conflicts stemming from the bipolar agricultural structure. In particular, European countries pushed ahead with agricultural reshuffling in pursuit of industrial efficiency until the 1970s. Thus, the current agricultural policy issue of the Government is to minimize negative aspects, such as conflicts within the agricultural society, while improving the agricultural structure. It is high time to realize agricultural efficiency by pursuing for industrial policy and social-welfare policy in parallel, and minimize class and regional conflicts within the rural community by coordinating right policies. In particular, it should implement the policies favoring the vulnerable classes and regions, such as the direct payment system.
Keywords: Bipolarization phenomenon; Agricultural structure; Agricultural restructuring policy; Social insurance system.; Bipolarization phenomenon; Agricultural structure; Agricultural restructuring policy; Social insurance system.